Pelindungan Hak Subjek Data Pribadi dalam Kebijakan Penggunaan Ulang Nomor Telepon Seluler Ditinjau Menurut Hukum Positif Indonesia - Khalda Alifia Azzahra; Sinta Dewi Rosadi; Tasya Safiranita Ramli (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2025)
The practice of reusing mobile phone numbers leads to the transfer of data from previous users to new users of the number, which poses potential risks to privacy and personal data security. This study aims to identify the legal protections for the rights of personal data subjects and the implementation of personal data protection by telecommunications service providers in the policy of reusing mobile phone numbers under positive law in Indonesia. This study uses a normative and comparative juridical approach method with a descriptive-analytical research specification. Data collection techniques are carried out through literature studies. The data analysis method used is qualitative juridical. The results of the study show that the lack of enactment of derivative regulations of the PDP Law can lead to errors and legal loopholes in the application of articles in the PDP Law and in the implementation of personal data protection. Compared to the regulations in Australia, Indonesia has not yet provided adequate protection for the rights of personal data subjects of users in the practice of reusing mobile phone numbers. This can be seen from the many problems that arise in this practice, so it is necessary to make special regulations that regulate the policy on the reuse of mobile phone numbers.